Neuroprotective and metabotropic effect of aerobic exercise training in female patients with type 2 diabetes mellitus - POLAT, MİNE GÜLDEN; TİMURTAŞ, EREN (My University, 2022)
Objectives We aimed to evaluate the effects of acute and chronic aerobic exercise on cognitive function and depression levels in patients with Type 2 Diabetes Mellitus (T2DM) and the changes in related neurotrophic and metabotropic factors. Methods Sixteen female patients (age=57.5 +/- 7.3) diagnosed with T2DM were included. A and B sections of the Trail Making Test (TMT) and Beck Depression Inventory (BDI) were used to assess executive function and depression states. Brain-derived neurotrophic factor (BDNF), nerve growth factor (NGF), irisin, total oxidant status (TOS), total antioxidant status (TAS), oxidative stress index (OSI), fasting plasma glucose, hemoglobin A1c, and high-density lipoprotein (HDL) cholesterol were analyzed in blood. Aerobic exercise intensity was applied at 50-70% of the maximal heart rate for 40 min/day, three days weekly on the treadmill. All evaluations were repeated after one exercise session, a 12-week exercise program, and after one year for follow-up. Results TMT-A (p=0.001) and TMT-B (p=0.002) values were increased following both acute and chronic exercise. BDI scores were decreased after long-term exercise (p=0.031). Measurement of metabolic parameters revealed positive changes in HDL cholesterol (p=0.044), TAS (p=0.005), and OSI (p=0.009) values after chronic period exercise. No significant difference was found in BDNF (p=0.271), NGF (p=0.230), and irisin (p=0.101) values after acute or chronic exercise, on the other hand. Conclusions Although aerobic exercise training had a positive effect on metabolic and cognitive outcomes, this effect was independent of neurotrophic and metabotropic factors. Regular and long-term aerobic exercise training has protective and regulatory functions in T2DM.
Keywords: Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Temel Bilimler; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Natural Sciences; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; Moleküler Biyoloji ve Genetik; Yaşam Bilimleri (LIFE); BIOCHEMISTRY & MOLECULAR BIOLOGY; MOLECULAR BIOLOGY & GENETICS; Life Sciences (LIFE); İlaç Keşfi; Yapısal Biyoloji; Moleküler Biyoloji; Klinik Biyokimya; Kanser Araştırmaları; Biyokimya; Yaşlanma; Biyokimya, Genetik ve Moleküler Biyoloji (çeşitli); Genel Biyokimya, Genetik ve Moleküler Biyoloji; Drug Discovery; Structural Biology; Molecular Biology; Clinical Biochemistry; Cancer Research; Biochemistry; Aging; Biochemistry, Genetics and Molecular Biology (miscellaneous); General Biochemistry, Genetics and Molecular Biology; aerobic exercise; cognition; depression; inflammation; neurotrophin; type 2 diabetes mellitus; NEUROTROPHIC FACTOR; BDNF; GLUCOSE; RISK